Studi Manajemen Energi di Rumah Sakit Prima Medika Denpasar - Rachmat, Cecep Yudhie; Kumara, I Nyoman Satya; Giriantari, I.A.D (Jurnal Teknologi Elektro; Vol 18 No 1 (2019): Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2019.v18i01.P04, 2019)
Abstract —Prima Medika Hospital is a nationally accredited hospital with the highest category or Plenary in 2016. With the highest patient visit rate of 59,289 people in 2017 and an average occupancy rate of 79.89% is entered into the ideal category with electricity consumption of 2,299,077 kWh / year. Electricity expenses come from 5 equipment groups, namely: lighting equipment group 20.08%, equipment for air arrangement system 56.12%, medical equipment 8.92%, office equipment 5.30% and utilities utilities 9.57%. From the initial energy audit calculation, the Energy Consumption Intensity index is 344.23 kWh / m² / year and this is included in the Intensive Energy category or shows wasteful energy use. Energy conservation efforts will be carried out on all equipment groups, especially to the equipment of the air structuring system which is the biggest energy absorber starting from the assumption of equipment operating hour patterns and then searching for energy-saving potentials starting from the lighting equipment group in the form of lamp replacement with Light type Emitting Diode, from the office equipment group with the control of operating hours of Dispenser equipment and from the group of air structuring equipment with the replacement of standard AC technology into AC inverters, the total potential of electricity energy savings was 613,813.2 kwh / year or 26.70% so if the proposed Energy Saving Opportunity can be implemented then the final value can be reduced to 252.33 kWh / m² / Year or included in the Energy Standard category or already efficient